2021
DOI: 10.3897/neobiota.65.63179
|View full text |Cite
|
Sign up to set email alerts
|

Competitive ability of native and alien plants: effects of residence time and invasion status

Abstract: Competition is commonly thought to underlie the impact of plant invasions. However, competitive effects of aliens and competitive response of natives may also change over time. Indeed, as with time, the novelty of an invader decreases, the accumulated eco-evolutionary experience of resident species may eventually limit invasion success. We aimed to gain insights on whether directional changes in biotic interactions over time or more general differences between natives and aliens, for instance, resulting from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…They found that competitive effects increased with residence time and suggested that this arises from a build‐up of biotic resistance by the native community. Furthermore, in a pairwise competition experiment, Sheppard and Brendel (2021) found that native Asteraceae tended to perform better with Asteraceae neighbors of increasing residence time (consistent with an increase in biotic resistance at the level of individual species), but only under certain soil conditions. However, our finding that naïve communities have similar competitive effects as experienced ones contradicts these findings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They found that competitive effects increased with residence time and suggested that this arises from a build‐up of biotic resistance by the native community. Furthermore, in a pairwise competition experiment, Sheppard and Brendel (2021) found that native Asteraceae tended to perform better with Asteraceae neighbors of increasing residence time (consistent with an increase in biotic resistance at the level of individual species), but only under certain soil conditions. However, our finding that naïve communities have similar competitive effects as experienced ones contradicts these findings.…”
Section: Discussionmentioning
confidence: 93%
“…This experimental study is based on a species‐for‐time approach, for which we chose 40 annual Asteraceae species, including recently introduced neophytes, archaeophytes, and natives that arrived in Germany after the last glacial maximum (10,000–12,000 years before present; see Brendel et al, 2021; Sheppard & Brendel, 2021; Sheppard & Schurr, 2019). Neophytes represent those alien species that were introduced after the discovery of America in 1492 AD (usually rounded to 1500 AD) and archaeophytes were introduced before that date (Pyšek et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Competition may occur between native taxa and the invading one, notably when the counter taxa are closely related, where they are expected to share resource requirements ( Zwerschke et al, 2018 ). This kind of scenarios have been well-documented in various organisms, such as ants ( von Aesch & Cherix, 2005 ), birds ( Koenig, 2003 ), molluscs ( Zwerschke et al, 2018 ), plants ( Leger & Espeland, 2010 ; Čuda et al., 2015 ; Sheppard & Brendel, 2021 ), etc ., and even inspired E. O. Wilson to coin in his “taxon cycles” hypothesis ( Wilson, 1961 ). Alternatively, if the involved taxa were previously allopatric populations or subspecies, gene flow may occur between taxa, resulting in changes in the genetic make-up of the local population ( Rhymer & Simberloff, 1996 ).…”
Section: Introductionmentioning
confidence: 82%
“…For instance, neonative populations of Dendroctonus frontalis , whose presence was recorded for the first time in New York and Connecticut in 2014 and 2015, respectively (Dodds et al, 2018, Table 1), are much less harmful than those of Dendroctonus ponderosae (Table 2), a species that was recorded outside of its native range since 1970 (Carroll et al, 2006; Cudmore et al, 2010). Residence time has been frequently used to predict range size (Allen et al, 2013; Desprez‐Loustau et al, 2010; Pyšek et al, 2015), abundance (Hamilton et al, 2005), population growth (Brendel et al, 2021) and even competitive ability (Sheppard & Brendel, 2021) of alien taxa, whereas a possible link between the time since introduction and impact dynamics has received far less attention. The use of residence time as a predictor of environmental impacts seems ripe for further investigations in both bark beetles and other taxonomic groups that have been established as alien or neonative.…”
Section: Discussionmentioning
confidence: 99%